2023
DOI: 10.1002/cam4.6374
|View full text |Cite
|
Sign up to set email alerts
|

Body composition is associated with disease aetiology and prognosis in patients undergoing resection of intrahepatic cholangiocarcinoma

Abstract: BackgroundBody composition alterations are frequent in patients with cancer or chronic liver disease, but their prognostic value remains unclear in many cancer entities.ObjectiveWe investigated the impact of disease aetiology and body composition after surgery for intrahepatic cholangiocarcinoma (iCCA), a rare and understudied cancer entity in European and North American cohorts.MethodsComputer tomography‐based assessment of body composition at the level of the third lumbar vertebra was performed in 173 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In recent years, the association between MAFLD and CCA was evaluated. In this regard, emerging risk factors like obesity, T2DM, and MAFLD were primarily associated with iCCA, while traditional risk factors such as biliary cysts, liver cirrhosis, HBV, and HCV infections were associated with both iCCA and eCCA [119] . Moreover, a recent study involving 173 patients who underwent liver resection for iCCA found a high prevalence of MAFLD, significantly correlated with changes in body composition such as sarcopenia and visceral obesity [120] .…”
Section: Hepatocellular Carcinoma and Cholangiocarcinomamentioning
confidence: 98%
“…In recent years, the association between MAFLD and CCA was evaluated. In this regard, emerging risk factors like obesity, T2DM, and MAFLD were primarily associated with iCCA, while traditional risk factors such as biliary cysts, liver cirrhosis, HBV, and HCV infections were associated with both iCCA and eCCA [119] . Moreover, a recent study involving 173 patients who underwent liver resection for iCCA found a high prevalence of MAFLD, significantly correlated with changes in body composition such as sarcopenia and visceral obesity [120] .…”
Section: Hepatocellular Carcinoma and Cholangiocarcinomamentioning
confidence: 98%
“…A single slice of the axial CT images was selected at the level of the third lumbar vertebra to determine SAT and VAT areas. SAT and VAT areas (cm 2 ) were defined as areas with CT attenuation values ranging from −190 to −30 HU and ranging from −150 to −50 HU, respectively (Figure 3) [7,9]. SAI and VAI were calculated by normalizing the SAT and VAT areas to height squares (cm 2 /m 2 ) [27].…”
Section: Adipose Tissue Imaging Parameter Measurementsmentioning
confidence: 99%
“…Furthermore, the body mass index (BMI), which is the most commonly used scale for defining obesity, has been shown to be a significant prognostic factor for predicting clinical outcomes in both intrahepatic and extrahepatic cholangiocarcinoma patients, demonstrating worse survival in patients with a higher BMI [3,4]. Because BMI may be overly broad due to its inability to differentiate adipose tissue mass from other tissue mass in the body, several studies have directly measured areas of subcutaneous (SAT) and visceral adipose tissue (VAT) using computed tomography (CT) images, with such studies finding that adipose tissue mass in the abdomen was significantly associated with survival [7][8][9]. At present, this relationship between adipose tissue mass and cancer progression is mainly attributed to inflammatory processes in the adipose tissue of obese patients [10].…”
Section: Introductionmentioning
confidence: 99%